Handbook of mathematical economics. Volume 2 (Amsterdam ; New York North-Holland Pub. Co., 1982)
The Handbook of Mathematical Economics aims to provide a definitive source, reference, and teaching supplement for the field of mathematical economics. It surveys, as of the late 1970's the state of the art of mathematical economics. This is a constan tly developing field and all authors were invited to review and to appraise the current status and recent developments in their presentations. In addition to its use as a reference, it is intended that this Handbook will assist researchers and students working in one branch of mathematical economics to become acquainted with other branches of this field. Volume 2 elaborates on Mathematical Approaches to Microeconomic Theory, including consumer, producer, oligopoly, and duality theory, as well as Mathematical Approaches to Competitive Equilibrium including such aspects of competitive equilibrium as existence, stability, uncertainty, the computation of equilibrium prices, and the core of an economy.
Mathematical Approaches to Microeconomic Theory. Consumer theory (A.P. Barten, V. Buhm). Producers theory (M.I. Nadiri). Oligopoly theory (J.W. Friedman). Duality approaches to microeconomic theory (W.E. Diewert). On the microeconomic theory of invest ment under uncertainty (R.C. Merton). Market demand and excess demand functions (W. Shafer, H. Sonnenschein). Mathematical Approaches to Competitive Equilibrium. Existence of competitive equilibrium (G. Debreu). Stability (F. Hahn). Regular economies (E. Dierker). Core of an economy (W. Hildenbrand). Temporary general equilibrium theory (J.-M. Grandmont). Equilibrium under uncertainty (R. Radner). The computation of equilibrium prices: An exposition (H.E. Scarf).
Includes bibliographical references and index.
Keywords: Economics, Mathematical; Electronic books